Persilangan dan karakterisasi Drosophila strain Normal dengan strain Black Vestigial - Safitri, Aulia Wulan (Maliki Interdisciplinary Journal, 2024)
Drosophila melanogaster, a common insect species that is generally harmless and feeds on fungi growing on fruits. Fruit flies are insects that reproduce easily. A single mating can produce hundreds of offspring, and a new generation can develop every two weeks. These characteristics make fruit flies highly suitable organisms for genetic studies. The reasons for using Drosophila melanogaster include their easy availability, which does not hinder research, their small size, and the ease of breeding them in laboratories. This research aims to determine the ratio of crossbreeding results between the Normal strain of Drosophila melanogaster and the Black Vestigial strain, including their reciprocal crosses. This study illustrates the events that occur from the crossbreeding of Drosophila melanogaster and explains how these crossbreeding results occur. Data collection was carried out using a scientific approach with two sets of variables. The first set acted as a constant, while the second set was used to measure differences in the multiplication and purification of Drosophila performed directly. Based on the research results, the total number of larvae from P2 and Reciprocal crosses was 60, the number of mature pupae produced was 12, and the total number of flies produced was 7, with 3 males and 4 females. The phenotype ratio for P2 Drosophila was 2:2, and the phenotype ratio for Reciprocal Drosophila was 3:1.